Assessment of the effects of environmental pollution on farming activities in Ondo State, Nigeria - Oluremi, Aminu Folsasade; Lanrewaju, Ladapo Hakeem (International Journal of Sustainable Agricultural Research, 2026)
The study examined the effects of environmental pollution on smallholder farming activities in Ondo State, Nigeria. Using a cross-sectional survey, 120 farmers were sampled with structured questionnaires to collect data on socio-economic characteristics, sources and levels of pollution, perceived impacts on crops and livestock, and mitigation strategies. Descriptive statistics and multiple regression analysis were used for data analysis. Results showed that agrochemical use (81.7%), water pollution from runoff (73.3%), soil erosion and land degradation (61.7%), oil exploration activities (59.2%), and emissions from livestock (56.7%) were the major sources of environmental pollution. The majority (76.7%) of farmers were exposed to some degree of environmental pollution, leading to reduced crop yields, poor soil fertility, water contamination, increased pest resistance, livestock health problems, and higher production costs. Regression analysis indicated that sex, education, household size, farm size, frequency of extension agents’ visits, major occupation, off-farm engagement, cooperative membership, access to credit, income, and proximity to pollution sources significantly influenced farmers’ exposure to pollution. Farmers adopted mitigation strategies including crop diversification, crop rotation, and soil conservation, though the use of organic methods, water treatment systems, and precision technologies remained low. The study concludes that environmental pollution poses significant economic and health risks to farmers and recommends integrated measures such as sustainable farming practices, farmer education, cooperative engagement, financial support, and enforcement of environmental regulations to mitigate pollution impacts and enhance agricultural productivity in Ondo State.